2018
DOI: 10.1074/jbc.ra117.000529
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the protein propionylation activity of the histone acetyltransferase MOF (males absent on the first)

Abstract: Short-chain acylation of lysine residues recently emerges as a group of reversible posttranslational modifications in mammalian cells. The diversity of acylation further broadens the landscape and complexity of the proteome. Identification of regulatory enzymes and effector proteins for lysine acylation is critical to understand functions of these novel modifications at the molecular level. Here, we report that the MYST family of lysine acetyltransferases (KATs) possesses strong propionyltransferase activity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…KAT8 is critical for histone H4K16 propionylation in vivo. In addition to H4K16 acetylation, KAT8 promotes histone propionylation in vitro (36), but it is unclear which lysine residue is propionylated, nor was the physiological relevance investigated. KAT8 is an H4K16 acetyltransferase (6, 7, 9), so we postulated that it is also required for H4K16 propionylation (H4K16pr).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KAT8 is critical for histone H4K16 propionylation in vivo. In addition to H4K16 acetylation, KAT8 promotes histone propionylation in vitro (36), but it is unclear which lysine residue is propionylated, nor was the physiological relevance investigated. KAT8 is an H4K16 acetyltransferase (6, 7, 9), so we postulated that it is also required for H4K16 propionylation (H4K16pr).…”
Section: Resultsmentioning
confidence: 99%
“…(Supplemental Figure 10B) to control H4K16 acylation during cerebral development ( Figure 8E). The potential of KAT8 to catalyze H4K16 propionylation is intriguing ( Figure 6, C and D, and Supplemental Figure 7, C and D) (36). The acetyl-CoA concentration is much higher than propionyl-CoA in vivo (56), so propionylation may function as a complementary mechanism under conditions when the propionyl-CoA level is elevated (Supplemental Figure 7E).…”
Section: Discussionmentioning
confidence: 99%
“…CBP and p300 are reported to catalyse propionyalation 226 , butyrylation 226 and crotonylation 233,234 , albeit with reduced efficiency compared with acetylation 235 . Similarly, MOF can reportedly catalyse propionyalation 236 and crotonylation 233 , GCN5 can catalyse succinylation 237 , and moZ 236 , HBO1 (reF. 236 ) and PCAF 238 can catalyse propionylation.…”
Section: Box 2 | Acylations Catalysed By Katsmentioning
confidence: 98%
“…Similarly, MOF can reportedly catalyse propionyalation 236 and crotonylation 233 , GCN5 can catalyse succinylation 237 , and moZ 236 , HBO1 (reF. 236 ) and PCAF 238 can catalyse propionylation. Recent structural studies of GCN5 have shown that the succinyl-CoA molecule binds to the same catalytic pocket as acetyl-CoA but buries deeper into the hydrophobic binding pocket 237 .…”
Section: Box 2 | Acylations Catalysed By Katsmentioning
confidence: 98%
“…This encourages investigation of MOF partner proteins and MOF targets outside of chromatin. Moreover, MOF has been implicated in catalyzing other –acyl chains such as crotonylation and propionylation . However, the precise contribution of MOF and its NSL complex members to non‐acetyl acylations needs further investigation.…”
Section: Nsl Complex At Chromatinmentioning
confidence: 99%